Caregivers’ Perception about the Relationship between Oral Health and Overall Health in Individuals with Disability in Qatif, Saudi Arabia: A Cross-Sectional Study - Marwa Alalshaikh; Rasha Alsheikh; Amal Alfaraj; Khalifa S. Al-Khalifa (International Journal of Dentistry, 2022)
Background. In Saudi Arabia, there are many people with disabilities that do not receive adequate healthcare, especially in the field of dentistry. Objective. This study focused on assessing caregivers’ perception of the relationship between oral healthcare and the overall health status of individuals with special healthcare needs (SHCN) in Qatif, Saudi Arabia. Methodology Design. This cross-sectional study was conducted using a questionnaire that was divided into two sections. The first part included demographic information such as the age and gender of both the caregiver and the person with a disability and the type of disability. The second part investigated the systemic health of the individual with a disability and the caregivers’ perception of the relationship between the management and treatment of systemic health and oral healthcare in relation to the overall health status. The results of descriptive analyses were summarized using frequency distribution tables. Bivariate analyses (chi-square test) were also performed. Significant differences were considered at a p value of 0.05. Setting. Initiated in school setting. Results. A total of 186 caregivers participated in the study. As much as 83.3% agree that oral health affects overall health, and 48.9% agreed that untreated dental problems could affect cardiac health. Age was the only factor found to be significantly associated with caregiver perception as younger caregivers were more likely to rightly understand the relationship between oral health and general health (p<0.05). Conclusion. This study has shown the extent to which caregivers of individuals with special care needs to understand the role of oral health in the general health of an individual. Three-quarters of the caregivers agree that dental health affects overall health, and age is a factor that might influence this understanding.